Adverse drug reaction to tremelimumab and durvalumab in hepatocellular carcinoma patients: an analysis of the food and drug administration adverse event reporting system database - Wei Fan Sui; Yu Xin Duan; Ze Feng Cai; Yi Mao Xia; Jian Yun Li; Jian Hua Fu (BMC Cancer)
Abstract Objective This study sought to comprehensively evaluate the safety profile of tremelimumab and durvalumab in patients with hepatocellular carcinoma (HCC) by examining adverse drug reaction (ADR) documented in the Food and Drug Administration’s Adverse Event Reporting System (FAERS) database. Methods Data from the FAERS database spanning from the first quarter of 2004 to the first quarter of 2025 were extracted, filtered, and standardized. The Reporting Odds Ratio (ROR) and Bayesian Confidence Propagation Neural Network (BCPNN) method were utilized to analyze the signal strength and identify potential ADRs. Results A total of 574 cases and 1,021 ADR reports were identified. Gastrointestinal disorders (15.65%, n = 188), hepatobiliary disorders (12.16%, n = 146), and general disorders and administration site conditions (11.74%, n = 141) emerged as the most frequently reported categories by system organ class (SOC). Death, diarrhea, and malignant neoplasm progression were identified as the three most common preferred terms (PT) based on reporting frequency. Immune-mediated ADRs with elevated ROR and BCPNN values were prevalent across multiple systems, particularly within the gastrointestinal (528.22, 9.03), hepatic (863.82, 9.70), cardiac (365.24, 8.49), endocrine (321.26, 8.31), and dermatological (744.71, 9.51) domains. Conclusion The study underscored the intricate safety profile of tremelimumab and durvalumab in HCC patients, characterized predominantly by immune-mediated toxicities and significant gastrointestinal and hepatobiliary risks. Utilization of drugs necessitated meticulous patient selection and a multidisciplinary management approach to optimize patient outcomes and mitigate ADRs.